Twitter como fuente de información y su incidencia en la agenda informativa de los periodistas de Diario "El Comercio", en el período de junio a diciembre del 2011. - Medina Flores, María Cristina (2012)
The research paper, "Impact of print media (newspapers La Prensa and Los Andes, section A) on the social inclusion of people with disabilities in Riobamba, during the period October 2009 - March 2010" focuses on the unequal treatment of the print media circulating in Riobamba to encontrarnoticias not relevant for this vulnerable group to enable them to present their abilities, skills and strengths. Research, encourages ethics and social contribution that the written media, must demonstrate in spaces where people can meet, reflect and analyze cases of people with disabilities, this in order to search the alternative readers aimed at the true social inclusion that goes beyond economic aid. Is based on the scientific method through observation, survey and interview, aimed at 366 people with disabilities, journalists of newspapers and concluded with siguienteresultado: Print media (newspapers La Prensa and Los Andes, section A) not affect the social inclusion of people with disabilities in Riobamba, because it highlights relevant aspects of social inclusion of people with disabilities, in most cases they are institutional or social support news. As input a sequence of topics referred to the fact that people with different capacities are subjects of rights with the need to coordinate local efforts to create circles of support and social recognition is proposed.